CRITICAL THINKING IN THE AGE OF MEDIA (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article discusses the importance of critical thinking in the modern media era, its development, and its impact on an individual's ability to interpret information accurately. In a time of increasing digital information flow, critical thinking is emphasized as a means for individuals to protect themselves from manipulative content and to form independent judgments.